Pengaruh Salep Ekstrak Biji Buah Mangga Arumanis (Mangifera Indica L ) Terhadap Penyembuhan Luka Eksisi Secara In Vivo - Ifmaily Ifmaily; Ulfa Anggraini; Putri Rizki Fitriani (Jurnal Ventilator, 2023)
Arumanis mango seeds (Mangifera indica L.) are organic waste, which in previous research contained many secondary metabolite compounds such as flavonoids and had very strong antioxidant activity. Arumanis mango seeds have the potential to heal wounds, including excision wounds. Excision wounds are characterized by the loss of a certain amount of tissue volume that can be filled with wound healing material. The aim of this research was to determine the effect of arumanis mango seed extract ointment on the healing of excision wounds, variations in concentration and histopathological features. The experimental animals were divided into 5 groups, namely the control group (ointment base), the arumanis mango seed extract group with concentrations of 2.5%, 5% and 7.5% and the comparison group (T® ointment). Applying is done 2 times a day for 14 days. The parameters observed were the percentage of wound healing, epithelialization time, and histopathology. Results from the average percentage of healing of excision wounds in the control group (82.4%), concentration 2.5% (85.5%), concentration 5% (90.5%), concentration 7.5% (92.1%) and comparison (95.3%). Results of epithelialization time in the control group (10 days), 2.5% concentration (9 days), 5% concentration group (7 days), 7.5% concentration group (7 days) comparison group (7 days). For histopathology, the scores for epithelialization, collagen fibers and fibroblasts were obtained respectively in the control group (2,1,2), 2.5% concentration (2,2,3), 5% concentration group (2,3,3), concentration group 7.5% (2,3,3) and comparison (3,2,2). The results of the one-way ANOVA test showed that administration of arumanis mango seed extract ointment significantly influenced the parameters of wound healing area and epithelialization time (p<0.05). The conclusion is that arumanis mango seed extract ointment is effective in healing excision wounds. The most effective group for healing excision wounds was the 7.5% concentration group, with good histopathological results.